Literasi Keuangan Digital Berbasis Artificial Intelligence Dan Kesiapan Karier Mahasiswa Pendidikan Ekonomi: Peran Edupreneurial Mindset Sebagai Variabel Mediasi - Rahmawati Sarizki Habie (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2026)
Digital transformation and the development of artificial intelligence (AI) have changed the way students learn, manage financial information, build employability skills, and design future career opportunities. Economic Education students are no longer expected only to become prospective economics teachers; they also need digital financial literacy, technological adaptability, and an edupreneurial mindset to participate in the digital education and economic ecosystem. This study aims to examine the effect of AI-based digital financial literacy on the career readiness of Economic Education students, with edupreneurial mindset as a mediating variable. This research employed a quantitative survey design. Simulated data were developed from 185 Economic Education students and analysed using linear regression and mediation testing. The research instrument consisted of three main variables: AI-based digital financial literacy, edupreneurial mindset, and career readiness. The results show that AI-based digital financial literacy has a positive effect on edupreneurial mindset. AI-based digital financial literacy also positively affects students’ career readiness. Furthermore, edupreneurial mindset mediates the relationship between AI-based digital financial literacy and career readiness. These findings indicate that students’ ability to understand digital finance and utilise AI should not only be directed toward technical skills, but also transformed into innovative, creative, and value-creating educational mindsets. The novelty of this study lies in integrating AI-based digital financial literacy, edupreneurial mindset, and career readiness within the context of Economic Education. This study recommends strengthening the Economic Education curriculum through digital project-based learning, fintech simulation, ethical AI use, and edupreneurship product development.